Food Consumption Behavior of Pakistani Students Living in China: The Role of Food Safety and Health Consciousness in the Wake of Coronavirus Disease 2019 Pandemic - Khayyam, Muhammad; Chuanmin, Shuai; Qasim, Haroon; Ihtisham, Muhammad; Anjum, Raheel; Jiaxin, Li; Tikhomirova, Anna; Khan, Nawab (Frontiers in Psychology, 2021)
The emergence of COVID-19 has considerably changed global food production, processing, and consumption at different levels. Sojourners are among those who have experienced a higher level of food insecurity during the crisis of the COVID-19 outbreak. The current research aimed to investigate the immediate consumption behavioral intentions of Pakistani international student's in the People's Republic of China (PRC) during the wake of COVID-19 pandemic. This study applied the Theory of Planned Behavior (TPB) and background factors of food safety and health consciousness that influence Pakistani student's consumption behavioral intention toward unfamiliar local food in China. A relational model was analyzed where food safety and health consciousness were hypothesized to serve as background variables associated with TPB components. Moreover, the indirect effects of food safety and health consciousness on behavioral intentions were assessed. The data was collected through convenience samples from 462 Pakistani international students and was analyzed through PLS-SEM. The results confirmed that food safety and health consciousness were positively associated with attitude, subjective norm, and perceived behavioral control. However, food safety and health consciousness were indirectly associated with behavioral intention through attitude and subjective norm only. The results highlighted the role of food safety and health consciousness as important antecedents of classical TPB components that affect intentions and behaviors to avoid unfamiliar local food in a migrated context. The present study provides enlightenment to those who aim to investigate the consumption behavioral intentions of sojourners in the wake of pandemic situation based on food safety and health consciousness. The findings of the current study are also applicable to general consumption patterns in the food sector.